Inbreeding Depression and Alternative Solution in Buffaloes - Lisa Praharani; Riasari Gail Sianturi (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Buff and dairy buffaloes have an important role in farming system to produce meat, milk, and fertilizer. Their productivity and population have been decreasing due to several reasons such as inbreeding depression and lack of sires. This paper presents alternative efforts to improve genetics of buffaloes through outbreeding fascilitated by artificial insemination (AI) and estrus synchronization to decrease inbreeding rates. Effort to reduce inbreeding depression is conducted by introducing new buffalo genes from distant populations known as outbreeding. Indonesian Research Institute for Animal Production has initiated an outbreeding program in buffalo through AI. The pregnancy rate varies between 40-80% using estrus synchronization with prostaglandin and fixed time AI. Outbred offsprings have higher growth performance and selling price than offsprings of natural breeding. The outbreeding program through AI in buffaloes need to be carried out sustainability to increase availability of qualified breeding stocks.